Diamondback moth (Plutella xylostella) population, damage, and parasitoids in South Sumatra brassica crops, Indonesia - SITI HERLINDA; MUHAMMAD ALFI SYAHRU RAMADHAN; WEI HONG LAU; DELLANIA EKA RINDIANI; CHANDRA IRSAN; ERISE ANGGRAINI; JELLY MILINIA PUSPITA SARI (Society for Indonesian Biodiversity, 2025)
Abstract. Herlinda S, Ramadhan MAS, Lau WH, Rindiani DE, Irsan C, Anggraini E, Sari JMP. 2025. Diamondback moth (Plutella xylostella) population, damage, and parasitoids in South Sumatra brassica crops, Indonesia. Biodiversitas 26: 6162-6173. Plutella xylostella, diamondback moth can cause up to 100% damage to brassica crops. This study evaluated the presence and performance of P. xylostella egg and larval parasitoids, analyzed parasitoid species diversity, and assessed pest populations and associated crop damage. Surveys were conducted in lowland and highland areas across five districts/cities (Lahat City, Pagaralam City, Muara Enim District, Ogan Ilir District, and Banyuasin District), encompassing 13 villages in South Sumatra, Indonesia. Four parasitoid species were identified: Trichogramma sp., Tetrastichus howardi, Diadegma semiclausum, and Cotesia plutellae. Egg parasitism was significantly higher during the vegetative stage (48.09%) compared to the generative stage (33.59%) (P=0.0054). Similarly, larval parasitism was greater in the vegetative stage (44.35%) than in the generative stage (21.90%) (P=0.00013). The highest larval damage occurred in the highlands, particularly Dempo Skyline Village, Pagaralam City (92.10%). The greatest egg population density was observed in Gn. Agung (72.00 eggs per 100 plants), while larval density ranged from 3.33 to 13.00 larvae per 100 plants. Parasitoid species occurred across sites, while P. xylostella infestation and feeding damage varied with location. Therefore, strategies to enhance parasitoid effectiveness through conservation and augmentation are necessary to reduce pest populations and protect brassica crops.